2020
DOI: 10.1111/pan.13875
|View full text |Cite
|
Sign up to set email alerts
|

Continuous costoclavicular brachial plexus block in a pediatric patient for postfracture rehabilitation

Abstract: The costoclavicular approach to the brachial plexus block has been recently described as a technique for anesthesia or postoperative analgesia of distal upper limb. In this article, we describe a case in which a continuous costoclavicular brachial plexus block was performed in a pediatric patient for conservative treatment of a traumatic radial fracture with severe elbow rigidity. Perineural catheter placement is a valuable option for pain control and functional prognosis during rehabilitation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 3 publications
0
3
0
Order By: Relevance
“…Luo et al [ 16 ] evaluated the non-inferiority of brachial plexus block via CCB and ISB in 212 patients in 2023, demonstrating that CCB could provide a nerve block method with fewer complications for high-risk patients undergoing shoulder surgery. Furthermore, several case reports [ 35 37 ] have shown that brachial plexus block via the costoclavicular space approach allows for drug spread to the supraclavicular area, meeting the needs of shoulder and upper-arm humerus surgery. Therefore, CCB surpasses the block range of the traditional subclavian approach and fulfills surgical requirements for the forearm and proximal upper arm, including the humerus and shoulder.…”
Section: Clinical Applications Of Ccbmentioning
confidence: 99%
See 2 more Smart Citations
“…Luo et al [ 16 ] evaluated the non-inferiority of brachial plexus block via CCB and ISB in 212 patients in 2023, demonstrating that CCB could provide a nerve block method with fewer complications for high-risk patients undergoing shoulder surgery. Furthermore, several case reports [ 35 37 ] have shown that brachial plexus block via the costoclavicular space approach allows for drug spread to the supraclavicular area, meeting the needs of shoulder and upper-arm humerus surgery. Therefore, CCB surpasses the block range of the traditional subclavian approach and fulfills surgical requirements for the forearm and proximal upper arm, including the humerus and shoulder.…”
Section: Clinical Applications Of Ccbmentioning
confidence: 99%
“…It is commonly used for treatment of chronic pain conditions such as complex regional pain syndrome [ 52 ], refractory phantom limb pain [ 53 ], advanced cancer [ 54 ], trigeminal neuralgia [ 55 ], and patients requiring prolonged postoperative analgesia for rehabilitation [ 56 ]. Continuous brachial plexus block is frequently employed for postoperative pain management and upper-limb rehabilitation exercises [ 37 , 58 , 59 ]. Due to the long block time, it can significantly reduce postoperative rebound pain [ 57 ] and promote recovery of postoperative function, thus improving patient satisfaction [ 43 ].…”
Section: Clinical Applications Of Ccbmentioning
confidence: 99%
See 1 more Smart Citation